In vivo activity of different feeding levels of Greater Celandine (Chelidonium Majus) extract on the growth performance and digestibility in broilers - Muhammad Usman Arain; Gulfam Ali Mughal; Shamsuddin Bughio; Muhammad Bilawal Arain; Farman Siyal; Muhammad Ali Arain; Saba Nawaz Arain; Sarfraz Ali Vessar (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
The present research work was conducted to investigate the effect of Chelidonium Majus Extract (CME) on growth performance and digestibility in broiler chickens In vivo. 100-day-old chicks were used in study. Distributed in to 4 groups i.e. (A, B, C and D) 25 chicks in each group with 5 replicates. Group A kept as control without supplementation of (CME), group B with 0.5ml/L, group C with 1ml/L and group D with 1.5ml of supplemented with CME. Our findings regarding growth performance showed significantly (P<0.05) highest live body and Feed Conversion Ratio (FCR) in the birds of group C followed by D and B as compared to A group, significantly (P<0.05) highest feed intake and dressing% was detected in various treated groups. Moreover, water consumption showed significantly (P<0.05) increase in birds in group B as compared to C, D and A groups. Whereas decrease in mortality percentage was recorded in groups B and C as compared to A and D groups, however difference was non-significant (P>0.05) between all treated groups. morbidity percentage showed significantly (P<0.05) increased in A group as compared to B, C and D groups. Relative organs weight, spleen weight remained unaffected between all treatment groups. highest relative weight of gizzards and heart was observed in all treated groups; Similarly, maximum relative weight of liver was observed in C and D groups followed by A and B groups. Furthermore, digestibility of various nutrients, dry matter, crude protein showed significantly (P<0.05) increased between various treatment groups, However, crude fiber showed non-significantly (P>0.05) difference in all treatment group. Likewise, ash matter was recorded significantly (P<0.05) increased in C and D groups as compared to B and A groups. Furthermore, economically proved that more profitable in group C followed by groups A, B and D. Based on above results, it was concluded that providing Chelidonium majus extracts at the dose of 1 ml/litter had the better impact on growth performance, enhance the digestibility of various nutrients and best for the health aspects of broiler without any adverse effects.